(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess students’ knowledge and acceptance of emergency contraception (EC). Subjects and Methods: A cross-sectional study was conducted on 286 students at Hanoi Medical and Pharmaceutical University – Vietnam National University. Results: About 38.8% of participants had used EC, while 61.2% had not. Regarding knowledge, 89.9% understood that EC does not prevent sexually transmitted infections, and 86.2% correctly identified EC methods. However, 40.6% were unclear about its effectiveness, and 44.1% did not understand its mechanism. While 89.2% believed EC is safe and effective when used correctly, 30.3% doubted its effectiveness, and 20.6% associated it with high-risk groups. Factors such as academic year, residence, and family background significantly influenced EC use. First-year students had the highest usage rate (58.3%), while sixth-year students had the lowest (37.3%). Urban residents used EC more (50%) than rural residents (32.2%). Those with separated parents had a higher usage rate (72.9%) than those from intact families (31.9%), and married individuals used EC more (53.5%) than singles (24.3%). Conclusion: EC use was 38.8%, with users showing higher acceptance. Despite relatively good knowledge, misconceptions persist, including infertility concerns (40.6%) and target user stereotypes (14.8%). Residence, marital status, and family background influenced EC use. Strengthening education and communication is essential to reduce stigma and improve awareness.